Predictive Modelling of Crime in Selected Nigerian Cities - adigun, folasade oyenike; Adedibu, Afolabi Adegbite; Abolade, Olajoke (Advances in Social Sciences Research Journal, 2016)
Using ten year police crime record (1999-2008), this study predicts future crime incidences and prevalence rates (2008-2050) for Ibadan, Zaria and Owerri. Linear Regression Analysis was used in determining the linear relationship between year and annual crime incidence. Crime incidence was taken as a quotient of projected population figure in order to establish predicted prevalence rates. The predictive models generated include y= -241278 + 123.8x (for Ibadan); y=83785.030 – 41.376x (for Zaria); y = -38897.3 + 19.727x (for Owerri) and y = 2003.128 + 0.0000537x (for the three cities as a whole). The predicted values reveals increase in crime trend in Ibadan from 7001 in 2008 to 12512 in 2050 and 903 in 2008 to 1544 in 2050 in Owerri but a decreasing crime trend in Zaria from 802 in 2008 to 5 in 2024. Between 2024 and 2025 crime trend in Zaria will reach zero point. The results further show a greater increase in Ibadan than the three cities as a whole. Between 2008 and 2050 residents of Ibadan, Zaria and Owerri will experience 108 – 258, -3 - 108 and 85 – 224 crime incidences per 1000 population, respectively. Taken the three cities as a representation of national crime situation, there will be 78 – 223 crime incidences per 1000 population in the nation between 2008 and 2050. The fact that a ‘zero point – crime incidence’ is a utopian situation ‘talk less’ of negative incidences suggested a caution in interpreting the trend of crime in Zaria. The crime situation in Ibadan and Zaria however needs urgent intervention from the residents and the government in order to avert increasing crime wave in the future.